2015
DOI: 10.1016/j.apradiso.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low background liquid scintillation counter for a shallow underground laboratory

Abstract: Pacific Northwest National Laboratory has recently opened a shallow underground laboratory intended for measurement of lowconcentration levels of radioactive isotopes in samples collected from the environment. The development of a low-background liquid scintillation counter is currently underway to further augment the measurement capabilities within this underground laboratory. Liquid scintillation counting is especially useful for measuring charged particle (e.g., β, α) emitting isotopes with no (or very weak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Although the ingrowth of daughters may need to be considered for correcting the observed activity to that of 227 Ac, it can be shown that over a 2083 min count time, only two daughters will have sufficient activity to contribute more than 1 % of the 227 Ac activity. One of these ( 227 Th) can be removed by alpha/beta discrimination and More detail on design considerations for reducing the background count rate is provided in [8] J Radioanal Nucl Chem the other ( 223 Fr) can be spectrally resolved due to a large difference in end-point decay energy from 227 Ac (1099 keV and 45 keV, respectively). In conclusion, a very low background LSC system may provide a practical means to take advantage of 227 Ac as a chronometer of deep ocean transport processes.…”
Section: Measurements Of 227 Acmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the ingrowth of daughters may need to be considered for correcting the observed activity to that of 227 Ac, it can be shown that over a 2083 min count time, only two daughters will have sufficient activity to contribute more than 1 % of the 227 Ac activity. One of these ( 227 Th) can be removed by alpha/beta discrimination and More detail on design considerations for reducing the background count rate is provided in [8] J Radioanal Nucl Chem the other ( 223 Fr) can be spectrally resolved due to a large difference in end-point decay energy from 227 Ac (1099 keV and 45 keV, respectively). In conclusion, a very low background LSC system may provide a practical means to take advantage of 227 Ac as a chronometer of deep ocean transport processes.…”
Section: Measurements Of 227 Acmentioning
confidence: 99%
“…More detail on design considerations for reducing the background count rate is provided in [8]. The values presented are based on seven replicate measurements and 21.5 % measurement efficiency a 1 TU (tritium unit) atomic ratio of tritium:hydrogen of 10 -18 , equivalent to 0.119 Bq/kg of water beads to increase the yield of combustion water, reduce the effect of color quenching, and reduce the quantity of sample needed to obtain sufficient analyte for a precision measurement.…”
Section: Determination Of Organically Bound Tritium (Obt)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, this lead was purchased in 2014 from Seafab Metals Company of Casa Grande, AZ. This lead was used in the construction of the middle layer of the shield for a low background liquid scintillation counter [16] located in the PNNL shallow underground laboratory [2] in Richland, WA.…”
Section: #4 -Doe Run (Seafab Vendor)mentioning
confidence: 99%